Two new species of the braconid wasp genus Bracon (Braconinae) from Los Tuxtlas region in Veracruz, Mexico, reared from fruits of three species of Lauraceae - Rodríguez-Sánchez, Edna; Giraldo-Kalil, Laura J.; Quicke, Donald L. J.; Zaldívar-Riverón, Alejandro (Zootaxa, 2022)
Two new species belonging to the braconid genus Bracon (Braconinae) are described from the tropical rainforest of Los Tuxtlas in the state of Veracruz, Mexico, B. laurae sp. nov. and B. rosamondae sp. nov. These species are morphologically similar and were reared from fruits of three Lauraceae species, Damburneya ambigens, D. salicifolia and Nectandra turbacensis. However, comparison of their DNA barcoding locus and a fragment of the nuclear ribosomal 28S gene confirmed their allospecificity. These two species share a number of morphological features with the two described Neotropical Bracon species that are known to be phytophagous (seed predators), B. phytophagus Quicke and B. zuleideae Perioto & Lara. We therefore propose a new species-group for the above four species, the B. phytophagus Quicke species-group, and suggest that the two newly described species also have a phytophagous feeding strategy.